2022
DOI: 10.3390/w14223621
|View full text |Cite
|
Sign up to set email alerts
|

IoT-Based Water Monitoring Systems: A Systematic Review

Abstract: Water quality monitoring plays a significant part in the transition towards intelligent and smart agriculture and provides an easy transition to automated monitoring of crucial components of human daily needs as new technologies are continuously developed and adopted in agricultural and human daily life (water). For the monitoring and management of water quality, this effort, however, requires reliable models with accurate and thorough datasets. Analyzing water quality monitoring models by utilizing sensors th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…This study used the Preferred Reporting Items for Reviews and Meta-Analyses (PRISMA) to conduct the investigation, as shown in Figure 3 [ 31 , 38 , 39 ]. The researchers avoided relying on a single database to find literature in the review article, as all relevant references may not be included, so a supplementary search is often necessary [ 32 , 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…This study used the Preferred Reporting Items for Reviews and Meta-Analyses (PRISMA) to conduct the investigation, as shown in Figure 3 [ 31 , 38 , 39 ]. The researchers avoided relying on a single database to find literature in the review article, as all relevant references may not be included, so a supplementary search is often necessary [ 32 , 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…This is well recognized by the EO community, using them for calibration/validation of satellite-based data and for covering the gap of data streams between two EO data observations. Wide-scale networks have been put in place for water quality monitoring in rivers [135], lakes [136], and marine environments [137].…”
Section: The Citizen Science and Iot Contributionmentioning
confidence: 99%
“…In addition to providing real-time data for flood prediction and water management, sensor-based monitoring systems also offer several other benefits. For instance, they provide a continuous and comprehensive data record that can be used for scientific research and policy-making [10].…”
Section: Burundimentioning
confidence: 99%